Reliable Monitoring Of Oxygen Saturation Via Pulse Oximetry: Which Site To Choose? - Juliana, N; Azmani, S; Idrose, A; Amirfaiz, S; Roslan, NA; Sulaiman, AH; Amin, NA; Fahmy, NIM; Rahman, HA (Univ El Oued, Fac Science & Technology, 2024)
Indexed by WOS